2018
DOI: 10.1149/2.0921816jes
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Response of Water in Deep Eutectic Solvent Based on Choline Chloride and Urea

Abstract: This work investigates the electrochemical role of water in the research of deep eutectic solvent (DES) based on urea and choline chloride. The motivation comes from the growing use of this DES, and on reports where a characteristic voltammetric cathodic pre-wave is observed. However, there has been no direct study to verify if such interpretation of the pre-wave is appropriate. In this regard, cyclic voltammetry has been used in this paper to interrogate the reactions inducing the appearance of the pre-wave. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In contrast to the results for ethaline, the effect of water on other DES systems, such as reline, can be significant [8,36]. For example, Du [8] reported that the electrochemical window reduced from 2.54 V to 1.03 V at a glassy carbon electrode when the water content was changed from 1 wt% to 12 wt%, similar to the range considered in this work.…”
Section: Effect Of Water On Electrochemical Windowsupporting
confidence: 59%
See 1 more Smart Citation
“…In contrast to the results for ethaline, the effect of water on other DES systems, such as reline, can be significant [8,36]. For example, Du [8] reported that the electrochemical window reduced from 2.54 V to 1.03 V at a glassy carbon electrode when the water content was changed from 1 wt% to 12 wt%, similar to the range considered in this work.…”
Section: Effect Of Water On Electrochemical Windowsupporting
confidence: 59%
“…In the absence of water, the anodic and cathodic limits are attributed to the reduction of the choline cation and the oxidation of Clto Cl2, respectively [8,10,36]. With added water, many other reactions are possible [10] and the situation for reline seems particularly complex [36]. It should be noted that even though conventional RTILs can have very large (e.g.…”
Section: Effect Of Water On Electrochemical Windowmentioning
confidence: 99%
“…In general, water in DES decreases its kinematic viscosity (Figure 5), increases its electrical conductivity, and notably narrows its electrochemical window [82,84], and all these factors contribute to the increase in the corrosion processes rate. Consequently, it was shown in [85] that the corrosion of mild steel in ethaline and reline is significantly enhanced even with the addition of only 10 wt.% of water.…”
Section: Effect Of Water Contentmentioning
confidence: 99%
“…11 It is well known that choline chloride based DESs are extremely hygroscopic mixtures, so they contain some percent of water, which is electroreduced at the cathode during the electrodeposition, by the same mechanism as in aqueous electrolytes. 12,13 Therefore, it would be interesting to calculate the pH change in the vicinity of the cathode during the electrodeposition process, and to compare the results for DESs with those for an aqueous solution.…”
Section: Calculation Of Surface Ph During the Electrodeposition Processmentioning
confidence: 99%